Liposarcoma. Clinical presentation and factors of pronostic value. Analysis of 35 cases - Viola, Alberto; Vasallo, Alberto; Nunes, Elía; de Stefanis, Eduardo; de Neo, Hugo; Coppola, Julieta (Cirugía del Uruguay, 1983)
... A retrospective study of 35 cases of liposarcomas is done. 27 superficial and 8 profound, retroperitoneal. The clinical factors of pronostic value are pointed out. ... A combined treatment ( sugery and radiotherapy) didn't modify the survival rate but. significantly decrease ( p;0.05) the frecuency of local recurrences.